INFLUENCE OF LEADERSHIP COMMITMENT TO GOOD CORPORATE GOVERNANCE AND BUDGET MANAGEMENT - Rana Kirana; Syarifah Hudayah; Irsan Tricahyadinata (Universitas PGRI Madiun, 2022)
This research aims to determine the influence of commitment to Good Corporate Governance and budget management. The measuring instrument used for data collection in this study is a structured questionnaire or questionnaire with closed questions in the form of a multilevel scale (rating scale), using data analysis with a Partial Least Square (PLS) approach. The results showed that, the leadership commitment variable has a positive and significant effect on Good Corporate Governance, the Leadership Commitment is proven to have a positive and significant influence on budget management, and Good Corporate Governance is proven to have a positive and significant influence on Budget Management. From the results of the research obtained several conclusions, among others, the better the commitment of the leadership, the commitment can determine success in budget management, realization and management of Good Corporate Governance through accountability, transparency, accountability, independence, and having equality and fairness in managing agencies properly will be able to improve budget management.